CFD results on hydrodynamic performances of a marine propeller - Loi, Luong Ngoc; Cong, Nguyen Chi; He, Ngo Van (Vietnam Journal of Marine Science and Technology, 2019)
In this work, the commercial Computational Fluid Dynamics (CFD), ANSYS-Fluent V.14.5 has been used to illustrate the effects of rudder and blade pitch on hydrodynamic performances of a propeller. At first, the characteristic curves of a container ship propeller are computed. Then, effects of rudder on hydrodynamic performances of the propeller in the both cases of the propeller with and without rudder have been investigated. The relationships between the blade pitch angle and the hydrodynamic performances of the selected referent propeller in this work having designed conditions as diameter of 3.65 m; speed of 200 rpm; average pitch of 2.459 m and the boss ratio of 0.1730. Using CFD, the characteristic curves of the marine propeller, pressure distribution, velocity distribution around propeller and the efficiency of the propeller have been shown. From the obtained results, the effects of rudder and blade pitch angle on hydrodynamic performances of the propeller have been evaluated.